Canadian permafrost stores large pools of ammonium and optically distinct dissolved organic matter - J. Fouché (Nature Portfolio, 2020)
Arctic warming leads to permafrost thaw and release of previously frozen organic matter and nutrients, but characterization of these pools is lacking. Here the authors use soil cores across Northern Canada to investigate dissolved organic matter and nitrogen stored in permafrost soils.